G319 A review of the quality of care following prolonged seizures in children with epilepsies. (7th April 2014) - Sidebotham, PD; Hunter, L; Appleton, R; Dunkley, C
Abstract : Objective: To review the quality of care of children and young people with epilepsies who received high-dependency or intensive care following a prolonged seizure. To identify and learn from any clinical, organisational, management or personal factors that contributed to these admissions, to inform clinical practice and to improve clinical services for children across the UK. Design: Notifications were collected from consultant paediatricians over 10 months. A clinical questionnaire was sent to the notifying clinician for all eligible cases. A sample of these cases was then selected for a detailed case note review. Case notes were reviewed by paediatrician-nurse pairs using a specifically-designed assessment tool derived from national guidelines. Setting: England, Wales, Scotland and Northern Ireland. Patients: Children between 1 and 18 years with a diagnosis of an epilepsy who received high-dependency or intensive care following a prolonged seizure. Results: Data were collected from 135 clinical questionnaires, and 36 sets of case notes were reviewed. Findings were compared to national standards of care and emerging themes identified. Thirty-two cases presented in the community, 15 of whom had a documented emergency care plan in the case notes but evidence that this had been followed only in five cases. Ambulance crews administered rescue medication in 13 cases: diazepam (rectal or intravenous) in 12 and buccal midazolam in one. The quality of emergency department care was judged to be excellent and meeting current best practice, or falling short in only minor areas, in 22 cases (69%), and that of intensive/high-dependency care in 26 cases (72%). In eight children (25%), the quality of emergency department care was considered to have fallen short of current best practice in one or more significant areas; that of intensive/high-dependency care in two cases. Conclusion: Findings suggest there have been improvements in the care of children and young people with epilepsies who present with prolonged seizures when compared to previous studies. However, further improvements are required in communication with families, the use of clear emergency care pathways, and prompt administration of emergency medication.